Accelerating progress on early childhood development for children under 5 years with disabilities by 2030. Issue 3 (March 2022) - ; Olusanya, Bolajoko O.; Boo, Nem Yun; Nair, M.K.C.; Samms-Vaughan, Maureen E.; Hadders-Algra, Mijna; Wright, Scott M.; Breinbauer, Cecilia; Almasri, Nihad; Moreno-Angarita, Marisol; Arabloo, Jalal; Arora, Narendra K.; et al.
Summary: The likelihood of a newborn child dying before their fifth birthday (under-5 mortality rate) is universally acknowledged as a reflection of the social, economic, health, and environmental conditions in which children (and the rest of society) live, but little is known about the likelihood of a newborn child having a lifelong disability before their fifth birthday if he or she survives. Available data show that globally the likelihood of a child having a disability before their fifth birthday was ten times higher than the likelihood of dying (377·2 vs 38·2 per 1000 livebirths) in 2019. However, disability funding declined by 11·4% between 2007 and 2016, and only 2% of the estimated US$79·1 billion invested in early childhood development during this period was spent on disabilities. This funding pattern has not improved since 2016. This paper highlights the urgent need to prioritise early childhood development for the beneficiaries of global child survival initiatives who have lifelong disabilities, especially in low-income and middle-income countries, as envisioned by the Sustainable Development Goals agenda. This endeavour would entail disability-focused programming and monitoring approaches, economic analysis of interventions services, and substantial funding to redress the present inequalities among this cohort of children by 2030.